(untitled) (Configurazioni. Research on contemporary poetry, 2023)
This paper investigates the critical reception of Dopo la lirica (2005) and Prosa in prosa (2009). By interviewing the editor of the first, Enrico Testa, and the authors, the (self)anthologized poets in the second text, it tries to clear the field from some reçues ideas and misunderstandings. It proposes to reconsider the break with the lyrical paradigm that some critical fringes have attributed to Testa and, besides, it highlights the reasons why Gherardo Bortolotti, Andrea Inglese, Marco Giovenale and Andrea Raos distance themselves from the anthological institute, preferring to ascribe Prosa in prosa to the category of a collective book.